DEVELOPING MATHEMATICS MODULE USING SCIENTIFIC APPROACH ON POLYHEDRON MATERIAL FOR DEAF STUDENT OF CLASS VIII IN SMPLB - B - Dwi Nurindahsari; Suparyan Suparyan (Universitas Ahmad Dahlan, 2018)
Every citizen is entitled to educational services despite limitations such as lack of hearing resulting in obstacles in communicating with the environment or often called deaf. The availability of teaching materials for deaf students is not yet available. It is one of the inhibiting factors of efficient and effective learning, hence the need for innovative, varied, contextual, and by the needs of the students. The aim of this research is 1) to design the mathematics module with scientific approach on the flat side room facet for the deaf students of grade VIII SMPLB-B, 2) to know the feasibility of the mathematics module by scientific approach on plyhedron material for the deaf students of class VIII SMPLB B. This study was a Research and Development with development model of ADDIE (Analysis, Design, Development, Implementation, Evaluation). The subjects were three expert teaching materials, two expert media modules, and four students of class VIII in SLB Negeri 2 Bantul, and two students of class VIII in SLB Wiyata Dharma I Sleman. Data collection techniques used were interviews and questionnaires. The research instrument used in the form of a questionnaire to expert assessment modules, expert teaching materials, and student response. Data were analyzed using qualitative descriptive analysis. Results of research and development showed that the mathematical e-module developed in the excellent category based on questionnaire assessment by expert instructional materials included in the first category with an average score of 84,6—the questionnaire results assessment by expert modules included in the good with an average score of 82.5. The questionnaire results by the joint expert media modules and expert materials included a good category with an average score of 83,8. At the same time, the results of student responses questionnaire in classes of test products included in the excellent categories with an average score of 85. The assessment results indicate that the math module with a scientific approach on the plyhedron material that had been developed fit for use in the learning process.